Analytical methodologies for the determination of biogenic amines in wines: an overview of the recent trends - Miranda, Andreia (2020)
Biogenic amines are naturally present in grapes or can occur during the vinification and aging processes, essentially due to the microorganism’s activity. When present in wines in high amount, biogenic amines may cause not only organoleptic defects but also adverse effects in sensitive human individuals, namely due to the toxicity of histamine, tyramine and putrescine. Even though there are no legal limits for the concentration of biogenic amines in wines, some European countries only recommend maximum limits for histamine. In this sense, biogenic amines in wines have been widely studied. The determination of amines in wines is commonly achieved by liquid chromatography, using derivatization reagents in order to promote its separation and detection. In alternative, other promising methodologies have been developed using capillary electrophoresis or biosensors, revealing lower costs and faster results, without needing a derivatization step. Nowadays, it is still a challenge to develop faster and inexpensive techniques or methodologies to apply in the wine industry. Thus, this review will be focused on the studies published in the last decade that involves the determination of biogenic amines in wines, highlighting the novelty, improvement and optimization of the analytical methods. The sample preparation procedures (such as derivatization reagents), the analytical methodologies and the new trends being followed by the wine industry are also described and discussed.